2011
DOI: 10.1002/cpp.703
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the panic disorder severity scale: clinician‐administered and self‐report versions

Abstract: The Panic Disorder Severity Scale (PDSS) is a seven-item scale designed to assess overall severity of panic disorder symptoms. Although the PDSS is widely used, there have been limited independent studies confirming reliability and validity, particularly of the self-report version of the PDSS, and even fewer studies directly comparing the two versions. Given the need for psychometrically sound measures that comprehensively assess the main features of panic disorder, this study examined the psychometric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…Items are rated on a 5-point Likerttype scale with higher scores indicating more severe panic symptoms. Prior psychometric research has indicated that the PDSS has good reliability and validity (Shear et al, 1997;Wuyek et al, 2011). The PDSS evidenced excellent internal consistency in the current sample (α ¼0.94).…”
Section: Fear Symptomsmentioning
confidence: 70%
See 1 more Smart Citation
“…Items are rated on a 5-point Likerttype scale with higher scores indicating more severe panic symptoms. Prior psychometric research has indicated that the PDSS has good reliability and validity (Shear et al, 1997;Wuyek et al, 2011). The PDSS evidenced excellent internal consistency in the current sample (α ¼0.94).…”
Section: Fear Symptomsmentioning
confidence: 70%
“…The Panic Disorder Severity Scale (PDSS; Shear et al, 1997;Wuyek et al, 2011) was used to assess symptoms of fear. The PDSS is a 7-item self-report questionnaire assessing severity and frequency of panic attacks, associated anxiety/distress, avoidance, and functional impairment.…”
Section: Fear Symptomsmentioning
confidence: 99%
“…(1) Panic Disorder Severity Scale (PDSS), which is a seven-item clinician-administered scale to assess overall panic severity [19,20]. The PDSS was rated before sessions 1, 5 and 10.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the clinician-rated measure, a selfreport format of the PDSS (PDSS-SR) is also available. The PDSS-SR was significantly correlated with clinician ratings on the PDSS (correlation = .61; Wuyek, Antony, & McCabe, 2011). This format has also been shown to have good test-retest reliability and is sensitive to change over the course of treatment (Houck, Spiegel, Shear, & Rucci, 2002;Wuyek et al, 2011).…”
Section: Composite Measuresmentioning
confidence: 86%
“…This format has also been shown to have good test-retest reliability and is sensitive to change over the course of treatment (Houck, Spiegel, Shear, & Rucci, 2002;Wuyek et al, 2011). However, the PDSS-SR was significantly less correlated with other panic-related measures, such as the ACQ and the MI, than the PDSS clinician-rated measure (Wuyek et al, 2011).…”
Section: Composite Measuresmentioning
confidence: 92%